Pengaruh Sales Promotion Golden Lamian di Instagram terhadap Keputusan Pembelian: Survei pada Followers Instagram @goldenlamian - Muhammad Fadli Alfaris; Oktaviana Purnamasari (STIKes Ibnu Sina Ajibarang, 2023)
New local brands are starting to enter the culinary industry so competition is increasing. Several culinary businesses in Indonesia are now thriving thanks to online media, such as Instagram and Golden Lamian. The purpose of this research is to measure @goldenlamian's sales promotion activities on Instagram, determine purchasing decisions, and the influence of sales promotions on Instagram on product purchasing decisions. The theory used is promotions in the form of coupons and special prices or discounts. Apart from purchasing decisions, there are also aspects related to problem recognition, information search, alternative evaluation, and purchasing decisions. This research method is quantitative using a survey method. 61 people were sent a questionnaire via the Instagram account @goldenlamian as part of the data collection strategy. Simple random sampling was used to take samples. The results of this research show that respondents responded (agree) to the Instagram sales promotion @goldenlamian. Meanwhile, the decision to purchase Golden Lamian received a good response (agree) with all variables (Y) in the research questionnaire. The Golden Lamian promotion influenced purchasing decisions by 32%, the remaining 67% was influenced by data from factors other than this research.